If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 3(5 + 6x) 2x = (5 * 3 + 6x * 3) 2x = (15 + 18x) Solving 2x = 15 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 2x + -18x = 15 + 18x + -18x Combine like terms: 2x + -18x = -16x -16x = 15 + 18x + -18x Combine like terms: 18x + -18x = 0 -16x = 15 + 0 -16x = 15 Divide each side by '-16'. x = -0.9375 Simplifying x = -0.9375
| 2b-b+5b=4a | | (-4+xyz)-(5+xyz)= | | 8x=4x-24 | | (7x+2y)+(-3y+x)= | | 4.9*x^2-13*x-23=0 | | 7y=6y-8 | | 3.01i-1.52i= | | p-30=6(h-6) | | -79h-(-9h)= | | -79h-(-9)= | | 5m=4m+7 | | 8x^3-24x^2+18x= | | 2z+6-z=5-9 | | 3.2a-16=14a | | x^2+5x+15=-4 | | 2z+6-z=5-4 | | 0=24t-.8t^2-90 | | 200+7x=6x | | y-7=-9 | | y-16=-9 | | -6y-8=9y+22 | | -3x-9y-6x+12y= | | am+14+1= | | 3x+5=4-(9x-8) | | z3-2=5 | | z/3-2=5 | | -2.1=n-7.5+0.8 | | 2x+37=90 | | 17+2x=31-2x | | 12(4+n)+5(-2n-9)=8 | | (5x^2+7x)(20x^2-11x-3)=0 | | 2a+1=148 |